Promoting caregiver involvement at the public library: An evaluation of a math and science storytime program for young children - Gaias, Larissa; Taylor, Michelle; Pratt, Megan E.; Whelan, Mariko (Frontiers in Psychology, 2022)
Public libraries are asset institutions that provide important spaces for families to engage in meaningful, authentic STEM learning. However, limited budgets and a model centered on open-access and broad inclusion makes conducting rigorous evaluations in these spaces, such as randomized control trials, challenging. There is a need to consider evaluation designs that consider both rigor and feasibility. The aims of the present study were to: 1) describe an innovative interactive parent-child interactive storytime program, Fun with Math and Science (FMS); and 2) conduct a preliminary evaluation of FMS in a large, urban public library setting, using a quasi-experimental static group comparison design. Post-test scores for caregivers who completed the program in the fall or winter (n = 80) were compared to pre-test scores for caregivers who completed the program the following spring (n = 35); Fall/winter caregivers scored higher on program items related to concrete behaviors to support math and science learning, but significant differences were not found on items related to caregiving beliefs or general caregiving practices. Demographic differences were also found related to program outcomes. Results are discussed both in terms of implications for the development and implementation of caregiver-child interactive programming, as well as the use of innovative analytic approaches to program evaluation in community settings.